(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
Folk believes are the residue of assembled experiences of a society which the concerned society gathers after a prolonged observation. There are many ethnic tribes all around the world who have followed their own folk beliefs. In a nutshell, folk believers always make an attempt to impart some sort of practical knowledge to its clansmen in order to run the tribe smoothly. This article makes a study of three prominent ethnic tribes from Assam i.e., Ahom, Mising and Deuri respectively with their own set of folk believes. While analysing their folk believes, this article studies the implications of prevailing folk believes of those tribes in connection to some of the essential issues including nature conservation, maintaining social discipline, providing moral education etc.